It's in Me to Give: Canadian Gay, Bisexual, and Queer Men's Willingness to Donate Blood If Eligible Despite Feelings of Policy Discrimination. (December 2020) - Grace, Daniel; Gaspar, Mark; Klassen, Benjamin; Lessard, David; Brennan, David J.; Lachowsky, Nathan J.; Adam, Barry D.; Cox, Joseph; Lambert, Gilles; Anand, Praney; Jollimore, Jody; Moore, David; et al.
Blood donation policies governing men who have sex with men have shifted significantly over time in Canada—from an initial lifetime ban in the wake of the AIDS crisis to successive phases of time-based deferment requiring periods of sexual abstinence (5 years to 1 year to 3 months). We interviewed 39 HIV-negative gay, bisexual, queer, and other sexual minority men (GBM) in Vancouver, Toronto, and Montreal to understand their willingness to donate blood if eligible. Transcripts were coded following inductive thematic analysis. We found interrelated and competing expressions of biological and sexual citizenship . Most participants said they were "safe"/"low risk" and "willing" donors and would gain satisfaction and civic pride from donation. Conversely, a smaller group neither prioritized the collectivizing biological citizenship goals associated with expanding blood donation access nor saw this as part of sexual citizenship priorities. Considerable repair work is required by Canada's blood operators to build trust with diverse GBM communities.